Meningkatkan Motivasi Belajar melalui Layanan Informasi dengan Media Komik - Ulfa, Marya; Awalya, Awalya (Indonesian Journal of Guidance and Counseling: Theory and Application, 2016)
This research implemented based on the phenomenon in VIII F grade of SMP Negeri 15 Semarang which shows that there are many students who has low learning motivation. The purpose of this research is to understand wheter the students learning motivation can be improved through the information services by using comics. The population is students of VIII F of SMP Negeri 15 Semarang that consists of 32 students and the sample is applied in all the population by using ‘jenuh sampling’ technique. The data collection technique uses a psychological scale of learning motivation and observation. While the data analysis technique uses the percentage of descriptive analysis and t-test. The result indicates that there is 20,34 % improvement of learning motivation after given some treatment of information services by using comics. Based on the t-test result, the value of tcount =48,802>ttable = 2,042 or it means that Ha is accepted and Ho is refused. Thus, the result of this research is learning motivation can be improved through the information services by using comics. Therefore, it is expected for teachers to give information services by using comics to students intensively as a strategy to help students learning motivation improvement.